Carbon emissions trading policy and green transformation of China’s manufacturing industry: Mechanism assessment and policy implications - Zhou, Zheng; Ma, Zichu; Lin, Xinwen (Frontiers in Environmental Science, 2022)
Accelerating the green transformation of manufacturing industry is the way to the sustainable development of China’s economy and an inevitable requirement for realizing the great vision of carbon peaking and carbon neutrality. This paper employs the global Malmquist-Luenberger productivity index based on the SBM-DEA method to calculate the green total factor productivity covering manufacturing industry of 30 Chinese provinces between 2006 and 2019. A difference-in-difference model is constructed to empirically study the direct impact and mechanism assessment of carbon emission trading policy on the green total factor productivity. The results show that the green total factor productivity of China’s manufacturing industry generally showed a dynamic trend of rising during this period. Critically, the implementation of the carbon emissions trading policy has a significant effect on promoting the green total factor productivity of China’s manufacturing industry. Interestingly, this promoting effect will be enhanced by higher technical levels, a cleaner energy structure, and a greener industrial structure. Additionally, our evidence also shows that the positive impact of carbon emission trading policies on green total factor productivity will be improved by higher carbon emission trading prices and a more active carbon emission trading market, thereby accelerating the green transformation process of manufacturing industry. Therefore, taking carbon emissions trading policy as a long-term strategy and improving its effectiveness is crucial to ensuring the green and sustainable development of China’s manufacturing industry.